2017
DOI: 10.1080/10410236.2017.1331188
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives of Oral Healthcare Providers’ Communication: Considering the Impact of Message Source and Content

Abstract: This study explores patients' perceptions of positive and negative communication experiences with dentists and dental hygienists using a sample of 267 individuals who reported having a general dental provider. Patients' oral health literacy, dental mistrust, use of dental health services, anxiety, and provider satisfaction are examined on the basis of reported communication experiences in the dental context. When comparing participants who had or had not experienced positive communication with a dentist, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…Third, there may be growing mistrust of dental professionals (Fico and Lagoe 2018). This mistrust is likely rooted in caregivers' concerns about unnecessary exposure to fluoride as well as suboptimal patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there may be growing mistrust of dental professionals (Fico and Lagoe 2018). This mistrust is likely rooted in caregivers' concerns about unnecessary exposure to fluoride as well as suboptimal patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding well-identified vulnerable groups, the presence of dental fear, along with sociodemographic difficulties and behavior management problems, were found to be indicative for dental health problems, ie, poor oral health.56 For instance, Chow and Cioffi57 found significant associations between increased activation of oral behaviors and trait anxiety, on the one hand, and the self-reporting of temporomandibular disorders on the other hand. However, there is also scientific evidence that good communication with the dentist attenuates the fear of dentist and is positively associated with higher levels of oral health literary.58 In addition, cognitive behavioral therapy was found to be effective in reducing dental anxiety in young patients 59…”
Section: Introductionmentioning
confidence: 99%
“…Items expressing more negative attitudes towards CSL (eg, that it is "too easy") more frequently yielded responses indicating neutrality (3) or disagreement (2), underscoring students' appreciation of the importance of CSL.…”
Section: Item Scoresmentioning
confidence: 99%
“…A systematic review of randomized, controlled trials found a significant relationship between physician‐patient communication and objective health outcome measures such as blood pressure . Similarly, positive dentist‐patient relationships improve patient oral health literacy and can help patients make positive oral health decisions . Relationships between dentist communication skills (CS) and subjective outcomes such as patient satisfaction have also been reported …”
Section: Introductionmentioning
confidence: 99%